2004
DOI: 10.1001/archopht.122.5.710
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric Analysis of Angiograms of Exudative Lesions in Age-RelatedMacular Degeneration

Abstract: Objectives: To analyze the morphometric composition of lesion components in exudative age-related macular degeneration and to study the relationships between individual lesion components and choroidal neovascularization (CNV) subtype, at 2 time points. Methods: Morphometric analysis of 98 sets of angiograms separated by an interval of at least 3 weeks, with no treatment delivered in the intervening period between angiograms. Area measurements of individual lesion components were made from digitally captured an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 12 publications
2
16
1
Order By: Relevance
“…31 This association, although not statistically significant, was also observed in another study that suggested that the presence of HE in NVAMD was related to large lesion size and occult leakage. 32 CNV and the total CNV lesion areas (comprising the CNV and confluent hemorrhage, blocked fluorescence, serous pigment epithelial detachments SPED ) in CATT were larger in eyes that had hard exudates. Occult type of CNV was also more common in eyes having HE although this was not statistically significant.…”
Section: Discussionmentioning
confidence: 89%
“…31 This association, although not statistically significant, was also observed in another study that suggested that the presence of HE in NVAMD was related to large lesion size and occult leakage. 32 CNV and the total CNV lesion areas (comprising the CNV and confluent hemorrhage, blocked fluorescence, serous pigment epithelial detachments SPED ) in CATT were larger in eyes that had hard exudates. Occult type of CNV was also more common in eyes having HE although this was not statistically significant.…”
Section: Discussionmentioning
confidence: 89%
“…According to the probability of CNV subtype conversion during/after ranibizumab therapy or over time, our cases might not reflect the characteristics of treatment‐naïve CNVs. A morphometric analysis of 98 sets of angiograms separated by an interval of at least 3 weeks, without receiving any treatment in the intervening period between angiograms showed that approximately 40% of lesions categorized as wholly classic CNV converted to predominantly classic CNV between baseline and the next follow‐up visit . Therefore, in our study, categorization of the CNV subtypes was based on the angiograms prior to initial ranibizumab therapy.…”
Section: Discussionmentioning
confidence: 98%
“…The lesion area was defined as the area of leakage caused by neovascularization and features obscuring the boundaries, including blocked fluorescence due to blood, thick exudate, hypertrophic retinal pigment epithelium (RPE), and associated pigment epithelial detachment (PED) on FA. The lesion area was measured in disc areas (DA), with one DA calculated as 2.54 mm 2 based on a standard disc diameter of 1.8 mm [1,18]. All cases were observed by optical coherence tomography (OCT) to confirm RPE elevation and retinal morphologic changes.…”
Section: Methodsmentioning
confidence: 99%